Substrates in ex vitro rooting of raspberry microcuttings (Research, Society and Development, 2022)
The objective of this work was to evaluate the use of different substrates in the ex vitro rooting of 'Fall Gold' raspberry microcuttings. The experimental design was completely randomized, with three levels for the factor substrates (vermiculite+coconut fiber Amafibra®, in proportion 1:1 v/cf; grape residue S10-Beifort® and carbonized rice husk). After 60 days, were evaluated the percentage of surviving seedlings, shoot length (cm), number of roots, length of the largest root (cm), fresh matter mass and shoot dry matter mass (g) and fresh matter mass and root dry matter mass (g). For the percentage of survival, shoot length, root length, shoot dry matter mass, fresh dry mass and root dry matter, there was no significant difference between S10-Beifort® and vermiculite+coconut fiber. However, both treatments differed statistically from the carbozinated rice husk, which showed the lowest averages. It is concluded that the use of the substrate S10-Beifort® or the mixture of vermiculite+coconut fiber are suitable for the rooting of 'Fall Gold' raspberry seedlings.